Going for a Song: The Cultural Politics of "Waltzing Matilda" - Seal, Graham (common Ground, 2013)
An examination of the copyright history of Australia’s unofficial national anthem, ‘Waltzing Matilda', provides an insight into the political, economic and cultural relations between Britain, the United States of America and Australia. In particular, the extent to which Australia’s cultural industries are a surrogate or proxy for the larger interests of global powers is demonstrated. It is argued that this surrogacy has, and continues to have, a potentially constricting effect on the circulation of matters of cultural concern through the Australian national community.